Foreign direct investment in Central Europe - Artur Dmochowski (Intereconomics, 1995)
Central European governments see foreign direct investment (FDI) as one of the main macroeconomic mechanisms for stabilizing the volatile process of economic and political transition. What are the favorite destinations of FDI in Central Europe? What are the motives of Western investors? Why does the amount of FDI vary so much between countries?
Keywords: 330